Analysis of effective numerical aperture in 2-D photonic crystal waveguide - Chantakit, T.; Kamoldilok, S.; Srinuanjan, K.; Yupapin, P. P. (My University, 2014)
The effective numerical aperture calculation in two-dimensional Photonic crystal waveguide has been proposed. In this paper we present the analysis of ray optics refracted inside nano rods and at the boundaries between rods, which separates rod gap is much smaller than the incident wavelength assumed to reflect on the region. In operation, the resolving numerical aperture was compared with the finite difference time domain method via OptiFDTD software. Although numerical aperture mentioned above was found to be extremely close to fiber optics, a transmission passes though compartments of the rods are observed due to significant estimation of transmission and reflection of electric field. The compared simulation results will be discussed. By the aforementioned is that in the near future we will modify wave equation in periodic media of waveguide structures reached to the transverse electric equation of beam propagation in the two-dimensional Photonic crystal waveguide analysed. © (2014) Trans Tech Publications, Switzerland.
Keywords: Numerical aperture; Photonic crystal; Waveguide